Agricultural water use and improving rural livelihoods in Sub-Saharan Africa: Current status, future directions, and the role of the International Programme for Technology and Research in Irrigation and Drainage (IPTRID). - International Water Management Institute (2003)
Its focus is on small-scale agricultural water use technologies (irrigation in its widest sense) in Sub-Saharan Africa. Section 1 provides an overview of the current status of natural resources, rural development and poverty, irrigation investment trends, and emerging new irrigation technology options. Section 2 discusses IPTRID's contribution to these emerging options. Section 3 proposes some ideas for consideration in terms of the future directions of IPTRID's work on small-scale irrigation in Sub-Saharan Africa.